Ultimate load prediction for timber beam - elasto-plastic theory approach - Abu Hassan, Suhaimi; Saleh, Abd. Latif; Mohamed, Zainai (2003)
Timber is one of engineering materials that behaves elasto-plastic property. However, the number of research that considers the elasto-plastic property of timber to analyse or to predict ultimate load of timber beam is limited. The application of perfectly elasto-plastic property for timber is proposed to predict the ultimate strength of solid and glulam beams. Three yield criteria for timber are introduced, i.e. yield criterion I, II and III. All criteria are developed based on orthotropic and microstructure property of timber. The existing criteria proposed by Tsai-Wu and Hill are also considered. These criteria were used to develop the theoretical model in order to predict the ultimate load of timber beams (solid and glulam). The ultimate loads predicted by perfectly elasto-plastic model (using yield criterion III) are in close agreement with experimental results. The predicted load-deflection curves using perfectly elasto-plastic model (using yield criterion III) is found to be approaching experimental load-deflection curves for most beams. Therefore this shows that the timber can be idealised as a perfectly elasto-plastic material. It can be concluded that the yield criterion III is the best criterion for solid and glulam timber beam. This new yield criterion is significant for development of theoretical model to predict ultimate load for timber beam.